Supervisors' Incentives and Job Satisfaction - Giroux, C.-Rodrigue (Relations industrielles / Industrial Relations, 1954)
SummaryIn the surveys made on the problem of job satisfaction, nobody has really questionned the necessity or the kind of relationship which should exist between the criterion and the attitude response. All the items of an attitude survey should be weighed according to their relative importance if the questionnaire is to be validated. Is there a relationship between the amount of satisfaction received from a group of incentives and the importance attributed to those incentives ? Can the present theories of human motivation explain that relationship ? The purpose of this study is an attempt to answer'the above questions. The author did it investigating operationnally for supervisors the kind of relationship which exists between the satisfaction received from certain incentives and the importance attributed to them.